Womenâ€™s Language in the Devil Wears Prada Movie Script By David Frankel - Ighfa Sakinah Yunnisa; Arman Arman; Neil Amstrong (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2020)
This study aimed to investigate and describe womanâ€™s language in the main character's The Devil Wears Prada movie script. The research question is â€œwhat are the features of womanâ€™s language described in The Devil Wears Prada movie script by David Frankelâ€?. The objective of this research is to describe ten types of womanâ€™s language features used by the main characters in The Devil Wears Prada. The Source of this data is taken from a movie script. The method used in this study was qualitative descriptive to analyze the data of Lakoffâ€™s theory. The data were taken from conversations uttered by the main characters of â€œThe Devil Wears Pradaâ€ movie script. The techniques of data analysis were presented, describing, interpreting, analyzing, and concluding the data. Based on the discussion, the researcher found several conclusions after analyzing this movie script. The researcher found ten types of womanâ€™s language used by the main characters in The Devil Wears Prada movie script there are lexical hedges fillers (3 data), tag questions (2 data), rising intonation on declarative (2 data), Empty Adjective (2 data), Avoidance of strong swearwords (3 data), Emphatic stress (2 data), super-polite form (2 data), precise color term (1 data), and intensifiers (2 data), and hypercorrect grammar (1 data) of the 20 data that are related to womanâ€™s language found in this movie script. This proves that womenâ€™s language exists in the conversations between the main characters in this movie script.